Situational Language Understanding in Texts - Neurohr, Benedict Jürgen (2021)
This thesis explores how human beings understand the language of fictional literary texts. The first half of the thesis explores the theory behind knowledge in the human brain, and introduces the concept of Predictive Coding and situation model theory. Using this, I present and discuss the theory which has arisen from my research on these topics, predictive model theory. Predictive model theory is used in chapter two to explore some linguistic phenomena which the theory can analyse and describe with great explanatory power. In chapter three in which I outline the main reasons why the theory is both a useful innovation to the field of literary linguistics and a powerful tool for explaining how texts can be understood in the face of ill-posed problems, fictional causality, and textual underdetermination. Following this, I introduce my own unique eye-tracking experiment, designed to look at predictive models in real fictional text, read by readers with a state of the art eye-tracker, which approximates natural reading. In the following discussion, the surprising results which show that a version of the text which is manipulated with logical inconsistencies is in fact read faster than a control. Using my predictive model theory, I discuss this further and offer suggestions of how this gives a brand-new insight into the reading process. I then introduce the concept of contextual plausibility, and how readers use specific indicators of causality and plausibility contained within texts, and integrate these into background knowledge of the world. In the next empirical chapter, my second eye-tracking study is introduced, which looks at how genre descriptions affect reading patterns of participants. Here I show that the unique difficulties faced by readers when part of the context of a textual extract do lead to a slowing down of the reading process. The following analysis delves further into the process of predictive situation models on a genre level. Finally, the conclusion summarises the unique findings of my theoretical considerations and the empirical data I have gathered to support them, and how this furthers the field of linguistics.